Interferon therapy of acute respiratory viral infections in children - A.E. Abaturov; E.A. Agafonova (Zaslavsky O.Yu., 2017)
The purpose of our study was to evaluate the efficacy and tolerability of nasal spray Laferobionum® (100,000 IU/ml) in children with acute respiratory viral infections. Materials and methods. The study included 84 children aged 12 to 18 years. Children of the main group (42 persons) received Laferobionum® spray in addition to the standard treatment for acute respiratory viral infections. The drug was administered to children of 12-14 years for 2 spray doses in each nasal passage 4-5 times a day at regular intervals (with the exception of sleep time), children aged 14-18 years received 3 spray-doses per each nasal passage 5-6 times a day at regular intervals (excluding sleep time). The course of treatment for all subjects was 5 days. Children of the control group received standard treatment for acute respiratory viral infections without Laferobionum®. Objective research included: auscultation of the heart and lungs, examination of the skin and mucous membranes, measurement of heart rate, blood pressure and body temperature. All patients underwent a general blood test, a general urinalysis, identification of the pathogen using the method of direct immunofluorescence (in smears taken from the nasal passages) in the laboratory "Medical Diagnostic Center of Dnipropetrovsk Medical Academy". Results. In the non-epidemic period, the respiratory syncytial virus and adenoviruses were the leading viral pathogens of acute respiratory viral infections. The main clinical manifestations of acute respiratory viral infection in the observed patients were signs of general inflammatory and catarrhal syndromes. All patients had not severe course of the disease. The data of the physical examination performed before the beginning of treatment indicated the absence of clinically significant deviations from the cardiovascular system in the children of the main and control groups. Arterial blood pressure and heart rate in the subjects of both groups were within the age limit and corresponded to the temperature response. Analyzing the dynamics of clinical symptoms of acute respiratory viral infection in both groups, it should be noted that there was a persistent tendency to lower body temperature in patients, both in the main and control groups. However, in the group of patients receiving Laferobionum®, the decrease in the temperature curve occurred faster, its normalization was noted already on the 4th day of therapy in 100 % of patients, whereas in the control group on the 4th day of the disease the body temperature remained subfebrile in 12 (28.6 %), on the 5th day - in 2 (4.8 %) children. Complete blood count in children of the main and control groups at the beginning of the disease showed leukopenia of varying severity, relative lymphocytosis, and accelerated erythrocyte sedimentation rate (ESR). On the 5th day of therapy in patients of the main group, the number of leukocytes was normalized, the relative lymphocytosis persisted against the background of a decrease in ESR. While in the control group, the number of leukocytes in peripheral blood remained lower with an elevated level of ESR. During the whole period of observation, the presence and nature of possible complications of acute respiratory viral infection was assessed. The total duration of the observation period was 14 days. During the observation period, no complications were detected in any of the patients in the main or control groups. During the time of the clinical trial, no adverse reactions were recorded that could be associated with the administration of Laferobionum®. There were no cases of exacerbation of existing chronic diseases in the children of the main group, while 1 (2.4 %) person from the control group had exacerbation of chronic tonsillitis. Evaluation of the effectiveness of therapy with the drug was carried out on the 5th day of treatment. Since one of the effectiveness criteria was the absence of clinical signs of the disease at the end of therapy, we calculated the proportion of patients in groups, who didn't have clinical signs of acute respiratory viral infection (more than 1 point) after 5 days of treatment. The effectiveness of therapy with Laferobionum® was 100 %. The effectiveness of treatment with Laferobionum® depended to some extent on the etiology of the disease: in acute respiratory viral infections caused by the respiratory syncytial virus, there was less significant effect of interferon therapy on the course of the disease than in acute respiratory infections caused by influenza and parainfluenza viruses. Given the absence of subjective complaints from the examinees and negative changes in an objective and laboratory examination, tolerability of treatment in all patients receiving Laferobionum® was regarded as "good". Conclusions. Interferon therapy, in particular the use of recombinant α-2b interferons (Laferobionum®), is one of the most important components of the treatment for acute respiratory viral diseases in children. The use of interferon for intranasal administration, which contributes to the sanogenesis of acute respiratory infections, will accelerate the process of recovery, prevent the development of bacterial complications.